2010
DOI: 10.1111/j.1365-3059.2010.02360.x
|View full text |Cite
|
Sign up to set email alerts
|

First report of peanut foot rot caused by Neocosmospora vasinfecta in mainland China

Abstract: In June 2009, disease symptoms on peanut (Arachis hypogaea) were observed in several fields in Huoping county, Guangdong Province. The characteristic symptoms were black rot of the basal stems and roots, with many orange-brown fruiting bodies on the diseased parts. Entire vines eventually wilted and died. The disease incidence reached as much as 30% in some fields, causing severe yield losses. A fungus was consistently isolated from the edge of lesions and grown on potato dextrose agar at 25°C. Mycelia were wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…5 -15.5µm whereas the ascospores of var. africana were more commonly found in the range of 9.5 -11.5µm, supported by Dau et al (2010), Fuhlbohm et al (2007) and Pan et al (2010). While this variation in size is an interesting feature between the two varieties, Cannon and Hawksworth (1984) also reported this difference as not statistically significant therefore is not relevant for distinguishing between varieties.…”
Section: Morphologymentioning
confidence: 84%
See 4 more Smart Citations
“…5 -15.5µm whereas the ascospores of var. africana were more commonly found in the range of 9.5 -11.5µm, supported by Dau et al (2010), Fuhlbohm et al (2007) and Pan et al (2010). While this variation in size is an interesting feature between the two varieties, Cannon and Hawksworth (1984) also reported this difference as not statistically significant therefore is not relevant for distinguishing between varieties.…”
Section: Morphologymentioning
confidence: 84%
“…There have been reports of peanut root and pod rot caused by N. vasinfecta in Taiwan (Huang et al 1992), Vietnam (Dau et al 2010) and China (Pan et al 2010;Gai et al 2011a;Sun et al 2011a) that have reported similar symptoms in the field and after inoculation of plants under controlled conditions. Neocosmospora vasinfecta has also been reported as a pathogen of chickpea in Pakistan (Ali et al 2011) and soybean in the United States of America (Gray et al 1980;Greer et al 2015), China (Gai et al 2011b) and South Korea (Sun et al 2014).…”
Section: Research Backgroundmentioning
confidence: 93%
See 3 more Smart Citations